Grief symptoms and difficult patient loss for oncologists in response to patient death. Issue 7 (14th March 2016) - Granek, Leeat; Ben‐David, Merav; Shapira, Shahar; Bar‐Sela, Gil; Ariad, Samuel
Abstract: Objective: The study aimed to explore oncologist's grief symptoms over patient death and to identify why and which losses are particularly challenging when patients die. Methods: The grounded theory method was used to collect and analyze the data. Twenty‐two oncologists were interviewed between March 2013 and June 2014 from three adult oncology centers in the north, center, and south of Israel. Oncologists were at different stages of their careers and varied in their sub‐specialties, gender, and personal and professional backgrounds. Results: Grief begun when the patient died, in anticipation of the patient's death, many days after the death, or when the patient received a poor prognosis. The phenomenological experience of grief for oncologists included behavioral, cognitive, physical, and emotional symptoms in response to patient death. Behavioral symptoms included crying and difficulties sleeping. Cognitive symptoms included self‐doubt and rumination about the patient and the care the patient had received before death. Physical symptoms included chest pain, fatigue, and general physical discomfort. Emotional symptoms included sadness, anxiety, helplessness, guilt, relief, irritability, and loss. Difficult patient loss was caused by patient‐related factors, family‐related factors, and disease‐related factors. Conclusions: Patient deaths result in behavioral, cognitive, physical, and emotional symptoms of grief in oncologists. These symptoms become particularly intense in the context of patient, family, and disease‐related factors. Educational and supportive interventions for managing grief related to patient death are needed in order to support oncologists in their emotionally and mentally taxing work. Copyright © 2016 John Wiley & Sons, Ltd.